Enhancing interfacial charge transfer on novel 3D/1D multidimensional MoS2/TiO2 heterojunction toward efficient photoelectrocatalytic removal of levofloxacin. (1st February 2019) - Zeng, Libin; Li, Xinyong; Fan, Shiying; Yin, Zhifan; Zhang, Mingmei; Mu, Jincheng; Qin, Meichun; Lian, Tingting; Tadé, Moses; Liu, Shaomin
Abstract: Structure-controlled visible light driven photo-anode with high catalytic performance, plays important roles in environmental pollutants treatment. In this work, a mild hydrothermal assisted anodization approach has been reported to design an integrated self-assembled 3D flower-like MoS2 /1D TiO2 nanotube arrays (NTAs) hierarchical electrode. The constructed multidimensional electrode not only broadened the absorption spectrum response range but also promoted rapidly electron-hole pairs separation, exhibiting the excellent photoelectron catalytic (PEC) performance and stability in the degradation of target pollutants, which the photocurrent conversion efficiency was 6.5 times higher than that of pure TiO2 . Furtherly, a comprehensive mechanism was proposed to explain the charge transfer on the interface of intimate integration of 3D/1D hybrid nanostructure towards PEC properties in terms of the energy band structures and DFT. Furthermore, the photo-generated active species (OH and O2 − ) have been proved by electron paramagnetic resonance spectroscopy and fluorescence probe over the composites. Thus, this work could provide an effective strategy to design multidimensional coupled heterojunction materials toward solar energy conversion for environmental purification. Graphical abstract: Image 1 Highlights: Multidimensional 3D/1D hybrid nanostructure was successfully synthesized. The path of interfacial charge transfer was fully demonstrated. Such a 3D/1D heterojunction electrode exhibited excellent PEC activity for LEV elimination.